Cardiac Metastasis from Myxoid Liposarcoma Managed Successfully with Chemotherapy and Radiotherapy: Case Report and Review of the Literature - Georgios M. Stergiopoulos; Brittany L. Siontis; Ivy A. Petersen; Matthew T. Houdek; Thanh P. Ho; Scott H. Okuno; Steven I. Robinson (Current Oncology, 2024)
Background: Liposarcoma, one of the most prevalent sarcoma histologies, is recognized for its tendency for extra-pulmonary metastases. While oligometastatic cardiac disease is rarely reported, it poses a unique challenge as oligometastatic sarcomas are often managed with surgical resection. Case Report: We present a case of a 62-year-old man diagnosed with an oligometastatic myxoid liposarcoma (MLPS) to the heart 19 years after the primary tumor resection from the lower limb. The metastatic mass, situated in the pericardium adjacent and infiltrating the left ventricle, was not managed surgically but with a combination of chemotherapy and radiotherapy. The patient’s disease remains stable to date, for more than 10 years. Literature Review: We conducted a review of the literature to determine the preferred management approach for solitary cardiac metastases of sarcomas. We also conducted an in-depth analysis focusing on reported cases of MLPS metastasizing to the heart, aiming to extract pertinent data regarding the patient characteristics and the corresponding management strategies. Conclusions: Although clinical diagnoses of solitary or oligometastatic cardiac metastases from sarcomas are infrequent, this case underscores the significance of aggressive management employing chemotherapy and radiotherapy for chemosensitive and radiosensitive sarcomas, especially when surgical removal is high-risk. Furthermore, it challenges the notion that surgery is the exclusive therapeutic option leading to long-term clinical benefit in patients with recurrent sarcomas.